Measurement Properties of the Wheelchair Skills Test Questionnaire for Powered Wheelchair Users - Rushton, Paula W. (Disabil Rehabil Assist Technol, 2014)
PURPOSE: To evaluate the test-retest reliability, concurrent validity and responsiveness of the Wheelchair Skills Test - Questionnaire (WST-Q) Version 4.1 for powered wheelchair users. METHODS: A volunteer sample of 72 community-dwelling, experienced powered wheelchair users, ranging in age from 50 to 77 years, participated in this study. Participants completed measures at baseline and 1 month later. RESULTS: Mean ± standard deviation total percentage WST-Q scores at baseline and 1 month were 83.7% ±10.9 and 86.3% ±10.0 respectively. Cronbach’s alpha was 0.90 and the 1 month test-retest intraclass correlation coefficient (ICC(1,1)) was 0.78 (confidence interval:0.68–0.86). There were no floor or ceiling effects. Percentages of agreement between baseline and 1 month for individual skills ranged from 72.2–100%. The correlations between the WST-Q and the objective Wheelchair Skills Test (WST), WheelCon and Life Space Assessment were r=0.65, r = 0.47 and r = 0.47 respectively. The standard error of measurement (SEM) and smallest real difference (SRD) were 5.0 and 6.2 respectively. CONCLUSION: The WST-Q 4.1 has high internal consistency, strong test-retest reliability and strong support for concurrent validity and responsiveness.